Indonesian Theatre Ten Years after Reformasi - Barbara Hatley (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2008)
Theatre contributed actively to the Reformasi movement of 1998 in Indonesia, as shows were staged that united students, NGO workers, artists and others in shared criticism of the Suharto regime and aspirations for change. Modern Indonesianlanguage theatre has a long history of political involvement. Developed among students in the Dutch colonial school system, its aim was helping create the Indonesian nation. This led to friction with other political groups and with state authorities. During the New Order regime, performances conveyed criticism that could not be expressed through other channels. In the post-Suharto era, however, when political criticism can be freely expressed and there is no united opposition movement to work with, theatre necessarily connects in a different way to its social context. In Central Java, where the writers research has been based, contemporary theatrical performances are characterised by a shared focus on local identity and community. Local culture is sometimes interpreted as the indigenous cultural forms of an area, but more often as the mixed local-global culture that residents practise today. The term community is used to refer to immediate neighbours and to people with shared interests and experiences, who both watch and actively perform in plays. Such developments in theatre are clearly shaped by the heightened awareness of local identity fostered by regional autonomy and by the ideology of participatory democracy. But how do theatrical activities connect to other social forces and with the structures of the regional autonomy system? Is there any sense of future direction in the current vibrant celebration of local identity? In what ways does theatre in other regions reflect local social conditions? These important questions remain to be explored.